CREATING AN ELECTRONIC TEXTBOOK ON THE SUBJECT OF INTRODUCTION TO MACHINE LEARNING - Xoliqov Rayimberdi Ochilovich; Ochilov Muzaffar Rayimberdi ugli; Ochilova Sojida Rayimberdi kizi; Shoniyozova Yulduz Kahramon kizi (Galaxy International Interdisciplinary Research Journal, 2022)
Introduction to machine learning is the development and consolidation of knowledge and skills in science for users who want to learn the subject. Another advantage is that this application can be implemented in higher education institutions and as a science manual.